“He lay still. It was all right. The bull was gone”–Programming an “amplification” of meaning in some examples of “paratactic” sentence combinations - Fiona Rossette (Corela)
Parataxis is a notion which generally applies to clause combining within the sentence. This article broaches the question of whether it can be applied between sentences. Certain sequences of sentences can be likened to the famous veni, vidi, vici as they involve a similar association of contextual variables, such as concision and repetition. At the same time, the specificity of the sentence break needs to be accounted for, in terms of informational focus and the types of meanings which are produced. Parataxis equates with what is described here as a “contrived disconnectedness” between sentences. It is analysed here as one of the parameters, or fixed variables, which contribute to a specific semantic program. The objective of such a program is actually to amplify the meaning potential of the space between the sentences.